Propositions, the paradox of analysis, and Milan Kundera’s author’s note - Terence Rajivan Edward (IJRDO- Journal of Educational Research, 2025)
I draw attention to how the paradox of analysis arises from Milan Kundera’s The Book of Laughter and Forgetting. I present a literary solution to the paradox of analysis in light of the book, and also raise a question of whether sentences across languages are expressing the same proposition, owing to differences in informativeness.